Prognostic Value of S100P Expression in Patients With Digestive System Cancers: A Meta-Analysis - Liu, Bi-Xia; Tang, Chao-Tao; Dai, Xi-Jian; Zeng, Ling; Cheng, Fei; Chen, Youxiang; Zeng, Chunyan (Frontiers in Oncology, 2021)
Background: Digestive system cancers (DSCs) are recognized as associated with high morbidity and mortality. S100P has been reported as a prognostic biomarker in DSCs, but its prognostic value remains controversial. Accordingly, we conducted a meta-analysis to explore whether S100P is correlated with overall survival (OS) of patients with DSCs. The relationship between S100P and clinicopathological features was also evaluated. Methods: We systematically searched PubMed, Embase, Web of Science, and Cochrane Library for eligible studies up to January 2020. A total of 16 publications with 1,925 patients were included. Results: S100P overexpression was associated with poor OS of patient with DSCs (HR=1.54, 95% CI: 1.14-2.08, P=0.005). When stratified by anatomic structure, S100P overexpression was associated with poor prognosis in non-gastrointestinal tract cancers (HR=1.98, 95% CI: 1.44–2.72, P < 0.001), but not in gastrointestinal tract cancers (HR=1.09, 95% CI: 0.66–1.81, P=0.727). When stratified by tumor type, S100P overexpression predicts poor OS in cholangiocarcinoma (HR=2.14, 95% CI: 1.30–3.50, P=0.003) and hepatocellular carcinoma (HR = 1.91, 95% CI: 1.22–2.99, P =0.005), but not in gastric cancer (HR=0.97, 95% CI: 0.65–1.45, P=0.872), colorectal cancer (HR=1.18, 95% CI: 0.32–4.41, P = 0.807), gallbladder cancer (HR=1.40, 95% CI: 0.84-2.34, P = 0.198), and pancreatic cancer (HR = 1.92, 95% CI: 0.99–3.72, P = 0.053). Furthermore, high S100P expression was significantly associated with distant metastasis (OR = 3.58, P = 0.044), advanced clinical stage (OR = 2.03, P = 0.041) and recurrence (OR = 1.66, P = 0.007). Conclusion: S100P might act as a prognostic indicator of non-gastrointestinal tract cancers.